2020
DOI: 10.1089/lap.2019.0701
|View full text |Cite
|
Sign up to set email alerts
|

Impact of First Assistant Surgeon Experience on the Perioperative Outcomes of Laparoscopic Hepatectomies

Abstract: Introduction: This study aims to evaluate the impact of first assistant surgeon experience on the outcomes of laparoscopic hepatectomies in a university-affiliated teaching hospital. Methods: This is a retrospective study comparing outcomes of laparoscopic hepatectomies with first assistant surgeons of varying experience levels. Three hundred and eighty-five consecutive laparoscopic hepatectomies performed in a tertiary university-affiliated teaching hospital from 2012 to 2018 were included and stratified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Notably, TLAP inevitably requires a surgical team that includes assistant surgeons. Although the auxiliary operators were inexperienced compared to the expert surgeon in this study, other studies have shown that a less-experienced assistant does not negatively affect perioperative outcomes ( 29 , 30 ). Moreover, the learning curve also partly reflected the tacit team cooperation in TLAP.…”
Section: Discussionmentioning
confidence: 80%
“…Notably, TLAP inevitably requires a surgical team that includes assistant surgeons. Although the auxiliary operators were inexperienced compared to the expert surgeon in this study, other studies have shown that a less-experienced assistant does not negatively affect perioperative outcomes ( 29 , 30 ). Moreover, the learning curve also partly reflected the tacit team cooperation in TLAP.…”
Section: Discussionmentioning
confidence: 80%
“…In surgeries for benign diseases, Tarik et al reported that the training level of the first assistant in bariatric procedures did not negatively affect the occurrence of serious perioperative complications [21]. In surgeries for malignant diseases, comparable results have been reported in laparoscopic sigmoidectomies and laparoscopic hepatectomies [14,22].…”
Section: Discussionmentioning
confidence: 93%
“…A primary surgeon may experience stress when working with an inexperienced assistant [ 14 ]. Cai et al described potential reasons why surgery with an inexperienced assistant does not affect the morbidity of complications [ 22 ]. First, the lack of experience of the first assistant surgeon could be offset by the rest of the surgical team.…”
Section: Discussionmentioning
confidence: 99%
“…In surgeries for benign diseases, Tarik et al reported that the training level of the rst assistant in bariatric procedures did not negatively affect the occurrence of serious perioperative complications [19]. In surgeries for malignant diseases, comparable results have been reported in laparoscopic sigmoidectomies and laparoscopic hepatectomies [12,20].…”
Section: Discussionmentioning
confidence: 93%
“…A primary surgeon may experience stress when working with an inexperienced assistant [12]. Cai et al described potential reasons why surgery with an inexperienced assistant does not affect the morbidity of complications [20]. First, the lack of experience of the rst assistant surgeon could be offset by the rest of the surgical team.…”
Section: Discussionmentioning
confidence: 99%